Diseconomies of Scale in the Hedge Fund Industry - TEO, Melvyn (Institutional Knowledge at Singapore Management University, 2012)
How does fund size impact fund performance in the hedge fund industry? We find unsurprisingly that fund size crimps both raw and risk-adjusted fund returns for the average hedge fund. An increase in fund assets under management from US$20m to US$1bn decreases fund alpha by 2.04 percent per year. However, significant variation exists across funds when funds are grouped by investment strategy and region. Equity long/short, event driven, and macro funds are susceptible to capacity constraints while fixed income and managed futures funds are largely immune to such concerns. Our finding that capacity issues impact macro fund performance raises fresh questions about the liquidity of the assets that macro funds trade. While we find that diseconomies of scale are pervasive across the majority of investment regions examined, it is surprising that funds operating in the Asian and Latin American markets are largely free of such constraints.